The coming generational storm : what you need to know about America's economic future - Kotlikoff, Laurence J. (MIT Press, 2004)
This paperback edition of The Coming Generational Storm has been revised and updated and includes a new foreword by the authors. In 2030, as 77 million baby boomers hobble into old age, walkers will outnumber strollers; there will be twice as many retirees as there are today but only 18 percent more workers. How will Social Security and Medicare function with fewer working taxpayers to support these programs? According to Laurence Kotlikoff and Scott Burns, if our government continues on the course it has set, we'll see skyrocketing tax rates, drastically lower retirement and health benefits, high inflation, a rapidly depreciating dollar, unemployment, and political instability. The government has lost its compass, say Kotlikoff and Burns, and the Bush administration's spending and tax policies have charted a course straight into the coming generational storm. Kotlikoff and Burns take us on a guided tour of our generational imbalance: There's the "fiscal child abuse" that will double the taxes paid by the next generation. There's also the "deficit delusion" of the under-reported national debt. And none of this, they say, will be solved by any of the popularly touted remedies: cutting taxes, technological progress, immigration, foreign investment, or the elimination of wasteful government spending. Kotlikoff and Burns propose bold new policies, including meaningful reforms of Social Security and Medicare, that are simple, straightforward, and geared to attract support from both political parties